Eudaimonia and the economics of happiness (2011)
In this paper I discuss the major approaches to happiness in the economics of happiness: hedonism and life-satisfaction approaches. It is possible to identify a tension between two important principles in this literature: 1) individuals are the best judges of their own happiness, and 2) the purpose of economics should be the direct endorsement of happiness. I argue that hedonism conflicts with the first principle. In the case of life-satisfaction theories, the restricted approach conflicts with both principles while the unrestricted approach only with the second. I also argue that the field presents difficulties establishing happiness as a consistent normative concept. In order to show this, I return to the theories of Aristotle and Seneca because: 1) both the ancients and these economists consider happiness as the overarching good; 2) even though these economists recognize the importance of eudaimonistic theories, their interpretation and use has not been satisfactory; 3) the debate between Aristotle and Seneca has implications both on the quantitative character of happiness and on the role of public policy regarding its promotion. The main lesson of the ancients is methodological: what made the discussion so rich among them was their awareness that happiness was principally a normative concept whose content had to adjust in order to meet its normative demands; a point contemporary literature seems to have missed.